Eunotia (Bacillariophyta) biodiversity from high altitude, freshwater habitats in the Mugecuo Scenic Area, Sichuan Province, China - Luo, Fen; You, Qingmin; Yu, Pan; Pang, Wanting; Wang, Quanxi (Phytotaxa, 2019)
Mugecuo Scenic Area is located in the northern Hengduan Mountains between the Sichuan Basin and the Qinghai-Tibet Plateau and has a subtropical humid monsoon climate. The area is at an altitude of 2600–3800 m above sea level (asl), with water originating mostly from melting mountain snow. In the region, a total of 20 Eunotia species have been identified, including two new species: E. mugecuo sp. nov., consisting of valves arched, clavate, ends broadly rounded, and terminal raphe fissures at the junction between valve face and mantle. The other newly-identified species is classified named as E. filiformis sp. nov., consisting of valves gently bent, ends not noticeably or only slightly inflated, broadly rounded, with external terminal raphe fissures curving in an angle of 180° back from apical nodules. Five newly recorded species have been identified in China, including E. odebrechtiana, E. michaelis, E. pomeranica, E. pseudogroenlandica and E. superpaludosa. Here, we discuss the new species and new taxon records through light and scanning microscopic documentation of valve morphology, along with key internal and external valve characteristics, and analyze the distribution of Eunotia in the Mugecuo Scenic Area.